INTERNATIONAL PRACTICE OF ASSESSING ECONOMIC SECURITY OF TERRITORIES AND SITUATION IN UZBEKISTAN (Marketing Journal, 2025)
The article analyzes international practices, existing approaches, and assessment systems related to regional economic security. Specifically, it examines strategic methods, indicator systems, and digital monitoring mechanisms used to ensure regional secur ity in developed countries (USA, Germany, Japan). The analysis focuses on key indicators such as regional GDP growth rates, investment activity levels, employment, and social stability indicators. In the case of Uzbekistan, the current practices and system ic shortcomings in assessing regional economic security are identified. Particular attention is paid to issues such as interregional disparities, unequal distribution of investments, and insufficient monitoring of economic risk factors. Based on internatio nal experience, the article concludes with recommendations to strengthen regional economic security in Uzbekistan. These include introducing modern assessment methodologies, establishing a regional digital monitoring system, and enhancing early -warning mec hanisms for economic risks.
Keywords: economic security; regional development; international experience; assessment methodology; systemic risks; stability index; strategic control; risk factors; digital monitoring; Uzbekistanʼs economic policy